ANALISIS DAYA SAING DAN FAKTOR-FAKTOR YANG MEMENGARUHI EKSPOR BAN INDONESIA KE KAWASAN AMERIKA LATIN - Mia Ayu Wardani; Sri Mulatsih (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2017)
The tire industry is an industry that has potential to increase Indonesian exports to non-traditional markets such as Latin America. The purpose of the study is to analyze the power of the comparative, competitive, and export dynamic of Indonesian tire and also the factors that affect the export of Indonesian tire to Latin America. The period of analysis used in this study is from 2009 to 2014 using the method of analysis are Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), Gravity models and Porter's Diamond. The results of this study are rubber tire Indonesia has strong competitiveness in Latin America than in the country of Argentina. In addition, the rubber tire Indonesia has a good export dynamics position (rising star) in the country of Panama, Venezuela, Uruguay, Mexico, Guatemala, and Costa Rica. Factors that affect the export of Indonesian rubber tire to Latin America is the distance economies, Indonesia's per capita real GDP, real GDP per capita of the destination country, the real exchange rate, and the population of the destination country.Keywords: Competitiveness, Gravity Model, Porter’s Diamond,Tire